2006
DOI: 10.1088/0953-2048/19/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thick PLD-GdBCO and ZrO2doped GdBCO coated conductors with high critical current on PLD-CeO2capped IBAD-GZO substrate tapes

Abstract: In order to increase the critical current, I c , we have fabricated thick GdBa 2 Cu 3 O 7−δ (GdBCO) coated conductors (CCs) by the pulsed laser deposition (PLD) method on PLD-CeO 2 /ion-beam assisted deposition (IBAD)-Gd 2 Zr 2 O 7 (GZO)/hastelloy metal substrate tapes. The highest critical current value was 522 A cm −1 for a thickness of 3.6 µm in self-field at 77 K. It was found that a low volume fraction of a-axis orientated grains was obtained in the thick GdBCO CCs, compared to YBa 2 Cu 3 O 7−δ (YBCO) CCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…To induce biaxial texture in buffer layers, two well established techniques have been explored to induce crystallographic alignment, i.e., incident substrate deposition [7,8] and ion-beam-assisted deposition (IBAD) [9e11]. In the IBAD approach, yttria-stabilized zirconia and Gd 2 Zr 2 O 7 are the mostly explored texturing materials [12,13]. Nevertheless, the slow evolution procedure of biaxial texture (with thickness >500 nm) for these fluorite-structured materials limits their application prospect.…”
Section: Introductionmentioning
confidence: 99%
“…To induce biaxial texture in buffer layers, two well established techniques have been explored to induce crystallographic alignment, i.e., incident substrate deposition [7,8] and ion-beam-assisted deposition (IBAD) [9e11]. In the IBAD approach, yttria-stabilized zirconia and Gd 2 Zr 2 O 7 are the mostly explored texturing materials [12,13]. Nevertheless, the slow evolution procedure of biaxial texture (with thickness >500 nm) for these fluorite-structured materials limits their application prospect.…”
Section: Introductionmentioning
confidence: 99%
“…5 In particular, columnar structures of 5-100 nm in diameter comprised of BZO nanodots, aligned along the c-axis of REBCO, can be formed in the PLD REBCO films. [6][7][8][9] These c-aligned columnar defects were found to be very effective in pinning, especially when the magnetic field B is applied parallel to the c-axis of REBCO. However, the aligned nanometer sized columnar defects were not previously observed in REBCO films grown by metal organic chemical vapor deposition ͑MOCVD͒, and the Zr doping was not substantially proven to enhance performance of MOCVD grown REBCO films until we recently demonstrated that the I c at 77 K and 1 T for MOCVD grown Zr:GdYBCO tapes could be of a factor of two higher than those for GdYBCO tapes without Zr-additions.…”
mentioning
confidence: 99%
“…4, the J c and the T c of the GdRE-123 films and Nd-123 film under magnetic field are plotted with our previous data of RE-123 [2,3,9,11]. The horizontal axis indicates ionic radius of the RE for the RE-123 or average ionic radius of the Gd and RE for the GdRE-123.…”
Section: Resultsmentioning
confidence: 97%